Ideas of jadidism and attempts to implement them in Karachay and Balkaria (1870s-1920s) - Muslim I. Barazbiev; Rustam M. Begeulov (Кавказология)
The article examines the public-educational views and activities of supporters of Jadidism in Karachay and Balkaria in the second third of the XIX–first third of the XX century. The data on specific personalities who tried to carry out some reforms in the system of Muslim education and enlightenment within the framework of this cultural and educational movement are given. Their efforts to modernize the local education system and introduce gender equality in this area, the development of the press, introducing the native language in spiritual and secular schools, etc. are highlighted. The activities of a significant part of the Karachay-Balkarian Jadids continued in the Soviet era, when many of them contributed significantly to the formation of a new school system in their native language. One of the key places in the article is occupied by the personality of Effendi, teacher, public figure Ismail Akbayev, who shared the ideas of the Jadids, tried to put them into practice and contributed significantly to the development of Karachay-Balkar culture, especially education. It is concluded that, thanks to the innovation of the Jadidids, advanced educational ideas for their time were embodied in the Karachay-Balkar ethno-cultural environment.